Monocyte progenitors give rise to multinucleated giant cells - Anne Kathrin Lösslein (Nature Communications, 2021)
Multinucleated giant cells characterize granuloma formation in mycobacterial infections. Here the authors identify monocyte precursors with distinct immunological and metabolic properties as a source of the granuloma multinucleated giant cell compartment.